PERSPEKTIF PENGEMBANGAN KOMPOS BIOAKTIVATOR UNTUK PENGENDALIAN Phytophthora capsici PADA TANAMAN LADA (Piper nigrum) - Jekvy Hendra; Widodo ;; Bonny P.W.S.; Bintoro H.M.; Manohara D. (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
Perspective on the Development of Bio-Activator Compost to Control the Attacks of Phytophthora capsici on Pepper (Piper nigrum). Bio-activator microbes can be found enormously in the compost, for instance bacteria (Bacillus spp., Pseudomonas spp), actinomycetes (Streptomyces spp.) and fungi (Trichoderma spp, Aspergillus spp, Penicillium spp). This research aimed to assess the development of bio-activator in controlling P. capsici and increasing production and quality of the pepper. Activity was done in the field trials in the upland and lowland as the center of pepper plants in Lampung using a factorial randomized design group with five replications. The first factor was microbial bio-activator formula and the second factor was three doses of compost namely 1, 2 and 3 kg/pepper plants. Each plant was given zeolite, which was 0.5 kg/tt and fulfat acid 1% as amount of 200 cc/tt. The study showed that microbial activators significantly suppressed P. capsici attacks and increased the production of pepper. In the uplands, the intensity of P. capsici decreased to 83.31%, while in the lowlands, the disease intensity that was caused by P. capsici decreased by 99-100%. The results of chemical and biological analysis of soil showed that the application of bio-activator compost increased the diversity of the types and the amounts of microbes in the rhizosphere as well as increased the nutrient availability. Combination treatment of bio-activator compost from coffee leather of 3 kg/tt were able to suppress the intensity of the disease BPB to more than 50% and increase the production of more than 30 %. Key words: piper nigrum, bioactivator, coffee skin, Phytophthora capsicii. Di dalam kompos banyak ditemukan mikroba bioaktifator, yaitu bakteri (Bacillus spp., Pseudomonas spp), aktinomiset (Streptomyces spp.) dan cendawan (Trichoderma spp, Aspergillus spp, Penicillium spp.). Bioaktivator dapat dimanfaatkan untuk mengendalikan serangan P.capsicii dan meningkatkan produksi serta mutu hasil lada. Kegiatan ini bertujuan mengkaji pengembangan bioaktivator untuk pengendalian Phytopthora capsici dan peningkatan produksi serta  mutu hasil lada. Pengkajian dilakukan dalam format uji lapangan didataran tinggi dan rendah sentra lokasi tanaman lada di Lampung. Pengkajian menggunakan Rancangan Acak Kelompok pola faktorial dengan lima ulangan. Faktor pertama ialah  bentuk formula  mikroba bioaktivator dan faktor kedua ialah tiga dosis kompos yaitu 1,2 dan 3 kg/tanaman lada. Setiap tanaman juga diberikan  zeolit 0.5 kg/tt dan asam fulfat 1% 200 cc/tt. Hasil pengkajian menunjukkan bahwa mikroba aktivator nyata menekan serangan P.capsicidan meningkatkan produksi lada. Di dataran tinggi intensitas serangan P. capsicimenurun hingga 83.31%, sedang  di dataran rendah intensitas serangan P capsicimenurun hingga 99-100%. Hasil analisis kimia tanah dan mikroba tanah menunjukkan bahwa aplikasi kompos bioaktivator meningkatkan keragaman jenis dan jumlah mikroba di dalam rhizosfer serta meningkatkan ketersediaan hara. Kombinasi perlakuan bioaktivator dan kompos kulit kopi 3 kg/tt mampu menekan intensitas penyakit BPB hingga > 50% dan meningkatkan produksi > 30%.   Kata kunci: Piper nigrum,  bioaktivator, kulit kopi, Phytopthora capsicii.